ACKNOWLEDGEMENTS AND CHECKLIST FOR ARTICLE CONTRIBUTORS - Holistics Journal Management (Politeknik Negeri Sriwijaya, 2019)
The Editor Board and Administrative Management of HOLISTICS Journal would like to extend their gratitude and appreciation to them for their scrupulous work in reading and reviewing the articles, and offering remarks and corrections for the betterment of the present issue. However, any possible deficiancy and negligence are the responsibility of the Journal Management.